PENGARUH PENGGUNAAN INTERNET TERHADAP PENJUALAN PROVIDER INTERNET DI MASA PANDEMI COVID-19 - Hidayah, Fitriana Nurochmatul; Maulida, Nur Arifah; Ghazi, Dhony Gymnastiar; Susanto, Yudha Mahendra Putra; Rakhmawati, Dwi Yuli (Jurnal Pendidikan Tata Niaga (JPTN), 2022)
The use of the internet is new, in the era of internet technology, it is one of the most important needs. Internet users are used to work, study, and social media. The use of the internet itself also affects the cultural changes that occur in a country, on the other hand the internet also has a positive impact on the progress of global science. We can see this from the development of the younger generation who can access the internet on a global scale. We have conducted a study of 39 adolescents on the use of the internet in daily life. In this study, the average teenager uses the internet as a medium for learning and working. Teenagers also use the internet to play online games, although the use of the internet for online games has a positive and negative impact from this making teenagers understand the impact of internet use. The sampling technique used was non-probability sampling. The technique used is simple linear regression analysis. This study shows a significant effect of internet use on internet provider sales during the COVID-19 pandemic, meaning that if internet usage increases, internet provider sales will also increase. Keywords: internet; internet usage; COVID-19; internet sales provider